The Principles of Price Formation in Medicine: an Attempt of Sociological Analysis on Example of Informal Money Payments in State Dentistry in Moscow - АлександроваЕлена Сергеевна (Journal of Economic Sociology, 2010)
The research focus of the paper is the process of price formation which is the core element for any market. The author tries to show how the price is formatted in the real market practices with help of informal medical services. Is it really so that the price behavior of market agents is defined only by costs saving and income increase from the professional activity or another factors play role as well (values, norms, traditions, social attitudes, affects)? The main goal of the survey is to disclose the guidelines of price formation for the informal payment in state Moscow hospitals formulated by the dentists for each client. The empirical basis is the in-depth interviews with state dentists who take informal payments and the quantitative information of the patients (their social, demographic, clinical characteristics and the price of the given medical services). The basis was collected within 30 days observation that three dentists agreed to participate in state dentist hospitals of Moscow.